Evaluating the Efficacy and Safety of a Nasal Medical Device (NESOSPRAY HE-G) in Acute Rhinosinusitis: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Marine Delmas; Manon D’Almeida; Séverine Dameron-Puech; Rémi Shrivastava (Medicina, 2026)
Background and Objectives: Acute rhinosinusitis is associated with a substantial deterioration in quality of life, including symptoms such as nasal obstruction, facial pressure, cough, and sleep disruption. Growing interest in non-pharmacological management strategies has been observed, particularly among populations in whom systemic treatments may be limited, such as pediatric patients and pregnant individuals. NESOSPRAY HE-G is a nasal device containing a filmogenic glycerol formulation designed to create a protective barrier and induce an osmotic effect, thereby promoting nasal decongestion and mucosal protection. Materials and Methods: A randomized, double-blind, placebo-controlled study was conducted to assess the performance and safety of NESOSPRAY HE-G (n = 20) compared with a saline comparator (n = 20) in patients aged 3 years and older presenting with acute rhinosinusitis and a baseline Rhino-Sinusitis Severity Score (RSSS) of at least 25/50. The investigational product was administered as three sprays per nostril, four times daily, over a maximum period of 15 days or until symptom resolution. Efficacy was primarily evaluated through changes in the total RSSS and in key symptoms, including nasal congestion, facial pain, cough, sleep disturbance, and fever. Safety assessments included monitoring adverse events (AE) and evaluating local tolerability. Results: Baseline characteristics were comparable between groups. Treatment with NESOSPRAY HE-G resulted in a statistically significant reduction in total RSSS from Day 2 onwards, with sustained effects throughout the study period. Improvements were also observed across individual symptoms, including early relief of nasal congestion and reductions in cough and facial pain, with faster onset compared to the comparator. Sleep quality showed progressive improvement. Resolution of fever occurred in both groups, with an earlier effect observed in the NESOSPRAY HE-G arm. No serious adverse events (SAE) or hypersensitivity reactions were reported. The product demonstrated good tolerability. Conclusions: NESOSPRAY HE-G provides rapid and sustained alleviation of symptoms associated with acute rhinosinusitis. Its topical mode of action, based on osmotic activity and barrier formation, represents a suitable non-pharmacological option, particularly for patients seeking alternatives to systemic therapies or presenting contraindications to such treatments.